The Influence of E-Service Quality, Sales Promotion and E-Security on Decisions to Use Lonline Delivery Message Service during Pandemic (Case Study of Go-Food Users) in Salatiga - Dewa Rendrahadi Wijaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The impact of Covid-19 has been felt in the food and beverages sector, which is mostly run by micro, small and medium enterprises (MSMEs) (Thaha, 2020). Gojek is an application that is currently being used by the public. The Go-food feature on Gojek makes food and beverages MSME businesses start to be helped by the e-service quality, sales promotion, and e-security offered by this application. This study aims to find the influence between the variables of e-service quality, sales promotion, and e-security with the decision to use the application. In this study, researchers used quantitative research. The population in this study were people in Salatiga who had used the Go-Food application. The number of samples used were 200 samples and the sampling technique used was purposive sampling and the instrument used in the questionnaire was the Likert scale. The data were tested using multiple linear analysis techniques. After testing, the results show that e-service quality, sales promotion, and e-security have a significant influence on decisions to use online delivery service applications.